2011
DOI: 10.1111/j.1464-410x.2011.10191.x
|View full text |Cite
|
Sign up to set email alerts
|

Two‐ and three‐/four dimensional perineal ultrasonography in men with urinary incontinence after radical prostatectomy

Abstract: and videos were also analysed by two independent investigators not present at the actual investigation. RESULTS• Using perineal ultrasonography we were able to visualize hypermobility of the proximal urethra, funnelling of the bladder neck, voluntary pelvic floor contraction, urethral and paraurethral fibrosis, and suture or sling material.• Men with and without PPI differed mainly in the degree of hypermobility of the proximal urethra and opening of the bladder neck.• Inter-investigator agreement was 100% in … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
32
0
1

Year Published

2012
2012
2022
2022

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 25 publications
(33 citation statements)
references
References 11 publications
0
32
0
1
Order By: Relevance
“…However, only LA activation has been analysed in this manner from ARJ, urethra and urethra-vesical junction (UVJ) movements using transperineal US in women 23, 24 . In men, quantification of UVJ motion with transabdominal 27 and transperineal 28, 29 US, and SUS motion with transurethral 26 and transrectal US 25 has been investigated. However, these studies only evaluated single structures, generally involved limited quantification of movements, and did not consider the relative contributions of the multiple striated muscles with potential to influence continence.…”
Section: Introductionmentioning
confidence: 99%
“…However, only LA activation has been analysed in this manner from ARJ, urethra and urethra-vesical junction (UVJ) movements using transperineal US in women 23, 24 . In men, quantification of UVJ motion with transabdominal 27 and transperineal 28, 29 US, and SUS motion with transurethral 26 and transrectal US 25 has been investigated. However, these studies only evaluated single structures, generally involved limited quantification of movements, and did not consider the relative contributions of the multiple striated muscles with potential to influence continence.…”
Section: Introductionmentioning
confidence: 99%
“…Kirschner-Hermanns et al performed a study on men after radical prostatectomy. They observed that 81% of the incontinent men had good or excellent voluntary muscle contraction compared to only 50% of continent men (13). There are only limited data comparing anatomical and physiological changes in men before and after radical prostatectomy.…”
Section: Discussionmentioning
confidence: 99%
“…The transducer was placed on the perineal area in a sagittal orientation, to obtain images of the pubic symphysis, bladder, bladder neck and urethra (13,16). Ultrasound assessment of the male bladder is best achieved when the urine volume is at least 300 mL.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations